Extra-parliamentarian political power and (social) media visibility. Issue 2 (4th May 2019) - Uldam, Julie
ABSTRACT: This article proposes a typology of extra-parliamentarian politics and access to parliament. On the basis of this, it discusses implications for reliance on (social) media visibility and its implications for (dis)empowerment. Theoretically, the article draws on media studies, social movement studies, political science and social theory, particularly conceptions of the public sphere, political participation and visibility. Empirically, it draws on examples of extra-parliamentarian political actors with little or no access to parliament and policy makers and illustrates the ways in which reliance on social media visibility is influenced by an interplay between access to parliament and degree of anti-systemicism.